2018
DOI: 10.15407/fm25.02.282
|View full text |Cite
|
Sign up to set email alerts
|

Effects of metal ion-doping on the characteristics and photocatalytic activities of TiO<sub>2</sub> nanotubes

Abstract: Ion-doped TiO 2 nanotubes were synthesized via a hydrothermal method and characterized by transmission electron microscopy, X-ray diffraction, X-ray photoelectron spectroscopy and specific surface areas. The binding energies of Cu 2+ , V 2+ , and Zn 2+ indicated that the doping ions existed as Cu 2+ , V 5+ , and Zn 2+ , respectively. With the increase of the calcination temperature, the intensity of the anatase phase decreased and the BET surface area decreased. The extent of anatase phase increased with the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…On the other hand, coupling with other semiconductors [27], plasmonic coupling with noble metals [28], or doping with different metallic and non-metallic atoms have also been employed to improve photocatalytic efficiency. Typically, nonmetallic elements such as C, N, S, P, and F can be used to substitute lattice oxygen anions [29][30][31], whereas metallic elements such as V, Cu, Zn, Bi, Co, and Fe substitute Ti cations [32][33][34][35]. These elements can create energy levels of the intermediate states in the band gap and act as electron trapper to inhibit the indirect recombination of photogenerated electrons and holes [36].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, coupling with other semiconductors [27], plasmonic coupling with noble metals [28], or doping with different metallic and non-metallic atoms have also been employed to improve photocatalytic efficiency. Typically, nonmetallic elements such as C, N, S, P, and F can be used to substitute lattice oxygen anions [29][30][31], whereas metallic elements such as V, Cu, Zn, Bi, Co, and Fe substitute Ti cations [32][33][34][35]. These elements can create energy levels of the intermediate states in the band gap and act as electron trapper to inhibit the indirect recombination of photogenerated electrons and holes [36].…”
Section: Introductionmentioning
confidence: 99%
“…Semiconductor TiO 2 has been known as a promising photocatalyst due to some of its qualities: abundance, lower cost, large surface area, nontoxicity, superior photostability, and so on. , However, previous studies have shown that, due to its wide band gap (about 3.2 eV), titanium dioxide can only absorb ultraviolet light (about 4% of solar energy). , Therefore, most of the light sources used in the current research on TiO 2 photocatalytic removal of Cr­(VI) are ultraviolet or sunlight. In recent years, in order to improve the utilization of TiO 2 -based catalysts for solar energy, researchers have made considerable efforts in extending the photoresponse of TiO 2 -based catalysts to the visible region, such as nonmetal doping, metal doping, precious metal deposition, structural heterojunction, and so on. Studies have shown that forming a heterojunction by combining TiO 2 with other semiconductors with narrow band gaps is a resultful method to increase the solar utilization of TiO 2 -based catalysts. ,, At present, graphitic carbon nitride (g-C 3 N 4 ) has been widely researched and concerned with for its low toxicity, low cost, visible-light-driven band gap, and long-term stability. Unfortunately, the photoreaction activity of pure g-C 3 N 4 is still unsatisfactory because it is affected by the weak van der Waals force between two adjacent planes, making the transfer process of photogenerated carriers slow down, resulting in electron–hole pairs recombining at a high rate. , At present, many attempts have been made by researchers to design the required g-C 3 N 4 –TiO 2 composites, since they have a structure overlapping with a matching, which facilitates the separation and transfer of photoinduced carriers, improving the photocatalytic activity of visible light. , However, the photocatalytic reaction efficiency of the binary catalyst still needs to be enhanced for practical applications because the photogenerated electron–hole pairs are still partially recombined at the two semiconductor interfaces. , Hence, it is urgent to improve the charge transfer kinetics of the g-C 3 N 4 –TiO 2 binary reduction of the accelerated photoreaction system to increase the photoreaction efficiency.…”
Section: Introductionmentioning
confidence: 99%